Analisis Pengembangan Smart Village di Desa Belalang Kabupaten Tabanan - Ni Made Pupuh Akasa Sari; Kadek Wiwin Dwi Wismayanti; Putu Nomy Yasintha (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
Smart Village is a concept where it adopts elements or components of the Smart City concept. From the six dimensions of Smart City, Smart Village adopting three dimensions, namely Smart Government, Smart Environment, and Smart People. The Smart Village development in Belalang Village, has been implemented since 2019, and has been developed in accordance with the three dimensions of Smart Village. This study aims to find out how to develop Smart Village in Belalang Village. In this study authors used a type of qualitative research with descriptive methods. The analysis in this research uses guide theory from Ramachandra which is, institutions, resources, technology, and sustainability. The results of the research show that the development of Smart Village in Belalang Village has been going well but not fully optimal. There are indicators that haven’t been implemented optimally because there are still several obstacles. The recommendations that can be given are making Smart Village regulations, IT staff can take part in additional training, and allocating funds to complete technology facilities.